A Study Of Site Planning Integrated With Sustainable Stormwater Management In The Scale Of District -Comparative Analysis Utilizing 3D Measurement Technology Part 1- - Shimazaki, Hikaru; Tanaka, Tomoaki (MAJ - Malaysia Architectural Journal, 2025)
With the recent increase of short-duration rainfall, the capacity of urban drainage tends to be exceeded, and inland flood is increasing. Particularly, in highly urbanized areas with low ground surface permeability, it is necessary to manage stormwater flows adequately. The site planning integrated with sustainable stormwater management both in the scale of building and district will become increasingly important. In this study, we focused one in the scale of district. We conducted surveys using 3D measurement technology, targeting two types in the scale of district: a case where sustainable stormwater management has been prepared in the Kamisakunobe area, Takatsu-ku, Kawasaki City, and a case where the sustainable stormwater management was not sufficiently prepared in Kuji area, Takatsu-ku, Kawasaki City. By analyzing and comparing the 3D data obtained from the surveys in the two cases, we aimed to clarify the effectiveness of stormwater management and damage by identifying the relationship between topographical features and the risks caused by them. First, for the Damaged case, we produced a 3D section of the damaged area and verified the relationship between the damage and the topography. Next, we verified the effectiveness of sustainable stormwater management for the Prepared case by following the same procedure. Then, we compared the two cases, and we examined how the site planning integrated with sustainable stormwater management can be effective in scale of the district.